Effect of supplementation with yeast polysaccharides on intestinal function in piglets infected with porcine epidemic diarrhea virus - Li, Hanxiao; Wu, Mengjun; Li, Zhonghua; Zhang, Qian; Zhang, Xiaohan; Zhang, Yanyan; Zhao, Di; Wang, Lei; Hou, Yongqing; Wu, Tao (Frontiers in Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) has caused huge economic losses to the pig industry. Yeast polysaccharides (YP) has been used as a feed additive in recent years and poses good anti-inflammatory and antiviral effects. The present study aimed to explore the protective effect of YP on intestinal damage in PEDV-infected piglets.Eighteen 7-day-old piglets with similar body weights were randomly divided into three groups: Control group (basal diet), PEDV group (basal diet), and PEDV+YP group (basal diet + 20 mg/kg BW YP ), six replicates per group and one pig per replicate. Piglets in PEDV group and PEDV+YP group were orally given PEDV (dose: 1×10 6 TCID50) at 19:30 PM on the 8th day of the experiment. the control group received the same volume of PBS solution. Weight was taken on an empty stomach in the morning of the 11th day, blood was collected and then anaesthetic was administered with pentobarbital sodium (50 mg/kg•BW) by intramuscular injection, and samples were slaughtered after the anaesthetic was complete. The results showed that YP could alleviate the destruction of intestinal villus morphology of piglets caused by PEDV. Meanwhile, PEDV infection can reduce the activity of glutathione peroxidase, superoxide dismutase and catalase, and increase the content of malondialdehyde. YP can improve the antioxidative capacity in the serum and small intestine of PEDV-infected piglets. In addition, YP inhibited the replication of PEDV in the jejunum ileum and colon. Moreover, YP can regulate the mRNA levels of inflammatory genes (IL-1β and iNOS) and lipid metabolic genes (APOA4 and APOC3) in the small intestine. In summary, YP could inhibit virus replicates, improve intestinal morphology, enhance antioxidant capacity, relieve inflammation and regulate the metabolism of the intestine in PEDV-infected piglets.